A novel static cultivation of bacterial cellulose production from sugar beet molasses: Series static culture (SSC) system - Oz, Yunus Emre; Kalender, Mehmet (Elsevier, 2023)
In bacterial cellulose (BC) production, we developed a new static cultivation system named series static culture (SSC) to eliminate air limitation problem encountered in conventional static culture (CSC). In SSC system, the fermentation broth at the bottom of BC pellicle produced in initial culture medium is transferred to the next empty sterile culture medium at the end of a certain fermentation period. This procedure was performed until BC production ceased. Fermentation experiments were carried out using Gluconacetobacter xylinus NRRL B-759 and sugar beet molasses at 30 degrees C and initial pH 5. Also, some quality parameters of produced BC pellicles were determined. Final pH at the stages of SSC system was higher that of the initial pH due to sugar content (sucrose) of molasses and microorganism used. Total BC production increased with increasing sugar concentration in SSC. As a result, an increase of 22.02 % in BC production was achieved using developed SSC. FT-IR spectra of all BC pellicles produced were typical spectra. The absorption bands at the relevant wavenumbers identify the mode of vibrations of the created chemical bonds arising at the BC surface such as O-H, C-H, H-O-H, C-O-C, and C-OH. XRD analyses showed that the crystallinity index values of BC obtained from CCS and SSC were high. The form of produced all BC pellicles is generally Cellulose I. Removal of surface moisture and depolymerisation of carbon skeleton were determined from TGA-DTA thermograms. SEM images showed that the BC samples produced had nano-sized cellulose fibrils which were aggregated in fermentation media containing molasses. Finally, the BC samples, especially in molasses media, having high mechanical strength and WHC were found.
Keywords: Series static culture; Bacterial cellulose; Sugar beet molasses; G; xylinus NRRL B-759; Characteristic parameters